Aplikasi Resep Camilan Bergizi Untuk Balita Menggunakan Metode Case Based Reasoning Berbasis Web Mobile (Information Technology and Telematics, 2015)
Abstract Snack food portions are smaller than usual meals. Useful snack for toddlers to avoid boredom eating patterns. Of the many problems that are difficult toddler eating or just want to consume certain foods, snack provision that meets the nutrient is also recommended. By utilizing the method of Case Based Reasoning and Nearest Neighbour algorithm, the authors implement an "Application Recipes Nutritious Snacks For Toddlers Based Mobile Web". The goal is to facilitate the public, especially parents in finding and making nutritious snack recipes. With input materials into form input material, after the input form is filled and processed materials it would seem the result of the similarity solution recipe recipe ingredient that has been entered. From the results of the recipes given solution will appear information about ingredients, how to manufacture, benefits, and the amount of nutritional value of recipes. Keyword : Toddler Snacks, Case Based Reasoning, Nearest Naeighbour, Mobile web